Psychic investigators : anthropology, modern spiritualism, & credible witnessing in the late Victorian Age - Sera-Shriar, Efram (Pittsburgh : University of Pittsburgh Press, 2022)
Psychic Investigators examines British anthropology's engagement with the modern spiritualist movement during the late Victorian era. Efram Sera-Shriar argues that debates over the existence of ghosts and psychical powers were at the center of anthropological discussions on human beliefs. He focuses on the importance of establishing credible witnesses of spirit and psychic phenomena in the writings of anthropologists such as Alfred Russel Wallace, Edward Burnett Tylor, Andrew Lang, and Edward Clodd. The book draws on major themes, such as the historical relationship between science and religion, the history of scientific observation, and the emergence of the subfield of anthropology of religion in the second half of the nineteenth century. For secularists such as Tylor and Clodd, spiritualism posed a major obstacle in establishing the legitimacy of the theory of animism: a core theoretical principle of anthropology founded in the belief of "primitive cultures" that spirits animated the world, and that this belief represented the foundation of all religious paradigms. What becomes clear through this nuanced examination of Victorian anthropology is that arguments involving spirits or psychic forces usually revolved around issues of evidence, or lack of it, rather than faith or beliefs or disbeliefs.
JSTOR
Keywords: Parapsychology -- Investigation -- Great Britain -- History -- 19th century; Anthropology -- Great Britain -- History -- 19th century; Spiritualism -- Great Britain -- History -- 19th century; Religion and science; Parapsychologie -- Enquêtes -- Grande-Bretagne -- Histoire -- 19e siècle.; Anthropologie -- Grande-Bretagne -- Histoire -- 19e siècle.; Spiritisme -- Grande-Bretagne -- Histoire -- 19e siècle.; Religion et sciences; SCIENCE; Spiritualism; Religion and science; Parapsychology -- Investigation; Anthropology; Great Britain; 1800-1899; Electronic books; History